2008
DOI: 10.1111/j.1467-8624.2008.01154.x
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Classroom Quality in Prekindergarten and Children’s Development of Academic, Language, and Social Skills

Abstract: This study examined development of academic, language, and social skills among 4-year-olds in publicly supported prekindergarten (pre-K) programs in relation to 3 methods of measuring pre-K quality, which are as follows: (a) adherence to 9 standards of quality related to program infrastructure and design, (b) observations of the overall quality of classroom environments, and (c) observations of teachers' emotional and instructional interactions with children in classrooms. Participants were 2,439 children enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
852
10
51

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,441 publications
(1,017 citation statements)
references
References 47 publications
50
852
10
51
Order By: Relevance
“…BM is indicated by clear expectations, attention to the positive behavior, and efficient redirection. Each dimension is scored on a scale ranging from 1 or 2 (low) to 6 or 7 (high) (see Mashburn et al, 2008).…”
Section: Classroom Qualitymentioning
confidence: 99%
“…BM is indicated by clear expectations, attention to the positive behavior, and efficient redirection. Each dimension is scored on a scale ranging from 1 or 2 (low) to 6 or 7 (high) (see Mashburn et al, 2008).…”
Section: Classroom Qualitymentioning
confidence: 99%
“…B. Ahnert, Milatz, Kappler, Schneiderwind & Fischer, 2013;Burchinal et al, 2008;Mashburn et al, 2008;O'Connor, Collins & Supplee, 2012). Ähnliche Befunde zeigten sich auch für die Lehrer-Kind-Beziehung im Grundschulalter (z.…”
Section: Introductionunclassified
“…Previous studies using the CLASS have yielded large-scale generalizable results on practices improving classroom quality (Hamre, Pianta, Mashburn, & Downer, 2007;Justice, Mashburn, Hamre, & Pianta, 2008). It is widely acknowledged that a higher quality of teaching further enhances children's academic and social development Mashburn et al, 2008), peer relations (Peisner-Feinberg et al, 2001), and children's motivation to learn .…”
Section: Classroomsmentioning
confidence: 99%
“…In studies on children aged 3 to 5 years, a high level of instructional support is associated with gains in language and mathematical skills Mashburn et al, 2008;Pianta & Hadden, 2008), as well as in-task behaviors having been observed more frequently in such classrooms (Pianta, LaParo, Payne, Cox, & Bradley, 2002). It has been suggested that teachers' provision of constructivist instructional exercises allowing preschool children's cooperation result in better language awareness (i.e., letter knowledge, word recognition, phonological awareness, and writing skills) than is the case for the more didactic drilling of basic skills (Korkeamäki & Goman, 2002).…”
Section: Instructional Support and Its Contribution To Children's Leamentioning
confidence: 99%